PLDAPS: A Hardware Architecture and Software Toolbox for Neurophysiology Requiring Complex Visual Stimuli and Online Behavioral Control - Eastman, Kyler M.; Huk, Alexander C. (Frontiers in Neuroinformatics, 2012)
Neurophysiological studies in awake, behaving primates (both human and nonhuman primates) have focused with increasing scrutiny on the temporal relationship between neural signals and behaviors. Consequently, laboratories are often faced with the problem of developing experimental equipment that can support data recording with high temporal precision and also be flexible enough to accommodate a wide variety of experimental paradigms. To this end, we have developed an architecture that integrates several modern pieces of equipment, but still grants experimenters a high degree of flexibility. Our hardware architecture and software tools take advantage of three popular and powerful technologies: the PLexon apparatus for neurophysiological recordings (Plexon, Inc., Dallas TX), a DAtapixx box (Vpixx Technologies, Saint-Bruno, QC, Canada) for analog, digital, and video signal input-output control, and the PSychtoolbox MATLAB toolbox for stimulus generation (Brainard, 1997). The PL-DA-PS (“Platypus”) system is designed to support the study of the visual systems of awake, behaving primates during multi-electrode neurophysiological recordings, but can be easily applied to other related domains. Despite its wide range of capabilities and support for cutting-edge video displays and neural recording systems, the PLDAPS system is simple enough for someone with basic MATLAB programming skills to design their own experiments.